Consumer Privacy and Data Tracking in the Digital Economy: Legal Frameworks and Future Challenges in Indonesia and Thailand - Agustianto Agustianto; Nipon Sohheng; Lu Sudirman; Triana Dewi Seroja; Nurlaily Nurlaily (Universitas Muhammadiyah Purwokerto, 2025)
This study analyzes the adequacy of consumer data protection frameworks in Indonesia and Thailand in addressing privacy threats posed by advanced tracking technologies through the lens of human rights. Using normative legal research methodology supported by a comparative approach, this study examines how both countries' legal frameworks govern data tracking technologies in their rapidly digitalizing economies. The analysis reveals significant weaknesses in both Indonesia's Personal Data Protection Law and Thailand's Personal Data Protection Act, particularly in their classification frameworks for advanced tracking technologies that combine machine learning algorithms with cross-device behavioral pattern analysis. While Thailand demonstrates superior protection against consent bundling, both countries lack comprehensive data classification systems and adequate mechanisms to address privacy threats from sophisticated tracking technologies. This study proposes a model of legal development to enhance consumer data protection in both jurisdictions, emphasizing the need for immediate reforms to protect privacy rights in the face of evolving digital tracking capabilities. The findings underscore the urgency for both countries to strengthen their legal frameworks to balance economic growth with fundamental human rights in the digital economy. The insights that this study provides contribute to the growing literature around consumer privacy, while also highlighting practical implications for Indonesia and Thailand, particularly regarding lack of data classification as a significant legal gap that both countries need to tackle.